Testing the Universality of the Gender Equality–Peace Thesis: The Influence of Increased Gender Equality on Terrorism in Turkey - Fisher, Daren (Women & criminal justice, 2019)
Gender inequality has been empirically linked to the incidence of terrorism, as a motivator for women’s involvement in terrorism, and political and social violence more generally. Although these studies demonstrate that advances in gender equality on average decrease terrorism, it is unclear how these influences translate to individual nations or conflicts. Because Turkey has witnessed consistent but unequal regional advances in gender equality, it provides an ideal setting to examine how these developments have influenced terrorist violence. Analyzing data from Turkey’s 81 provinces from 2000-2013, this study finds important regional differences in the influence of gender equality on terrorism.